Emerging Microfluidic Approaches for Platelet Mechanobiology and Interplay With Circulatory Systems - Zhang, Yingqi; Ramasundara, Savindi De Zoysa; Preketes-tardiani, Renee Ellen; Cheng, Vivian; Lu, Hongxu; Ju, Lining Arnold (Frontiers in Cardiovascular Medicine, 2021)
Understanding how platelets can sense and respond to hemodynamic forces in disturbed blood flow and complexed vasculature is crucial to the development of more effective and safer antithrombotic therapeutics. By incorporating diverse structural and functional designs, microfluidic technologies have emerged to mimic microvascular anatomies and hemodynamic microenvironments, which open the floodgates for fascinating platelet mechanobiology investigations. The latest endothelialized microfluidics can even recapitulate the crosstalk between platelets and the circulatory system, including the vessel walls and plasma proteins such as von Willebrand factor. Hereby, we highlight these exciting microfluidic applications to platelet mechanobiology and platelet–circulatory system interplay as implicated in thrombosis. Last but not least, we discuss the need for microfluidic standardization and summarize the commercially available microfluidic platforms for researchers to obtain reproducible and consistent results in the field.